Recombinant factor VIIa - Franchini, Massimo; Zaffanello, Marco; Veneri, Dino (Thrombosis and Haemostasis, 2005)
Recombinant activated factor VII (rFVIIa, Novo Seven®) has been successfully used to treat bleeding episodes in patients with antibodies against coagulation factors VIII and IX. In recent years, rFVIIa has also been employed for the management of uncontrolled bleeding in a number of congenital and acquired haemos- tatic abnormalities. Based on a literature search, this review examines the current knowledge on therapy with rFVIIa, from the now well-standardized uses to the newer and less well-characterised clinical applications.
Keywords: Recombinant FVIIa; bleeding; haemophilia; inhibitors